Song of Songs : Erotic love poetry, Judith Ernst : book review - Branch, Robin Gallaher (Old Testament essays, 2005)
Extracted from text ... Ernst, Judith 2003. Song of Songs: Erotic love poetry. Grand Rapids, MI: Eerdmans. 96 pages. Hardback with dust jacket. Price not mentioned. ISBN 0-8028-3990-8. Song of Songs: Erotic love poetry adapted and illustrated by Judith Ernst is a better gift for a wedding present than for an addition to the library of an academic. However, if the academic's office is large, it would do well on a coffee table and would be skimmed and enjoyed by visitors, for ..